Artifact Reduction in the Diagnosis of Vasospasm in Computed Tomographic Perfusion: Potential of Iterative Metal Artifact Reduction. Issue 4 (July 2019) - Hauser, Till-Karsten; Oergel, Anja; Hurth, Helene; Ernemann, Ulrike; Seeger, Achim
Abstract : Objective: This study aimed to analyze the possibility of artifact reduction using a new iterative metal artifact reduction algorithm (iMAR) in the diagnosis of perfusion deficits due to vasospasms and to evaluate its clinical relevance. Methods: Sixty-one volume perfusion computed tomographies of 24 patients after coiling or aneurysm clipping were reconstructed using standard-filtered back-projection and iMAR retrospectively. The degree of artifacts was evaluated as well as the size of the nonevaluable area. Diagnostic performance was evaluated compared with digital subtraction angiography. Results: Artifacts were present in 39 of 61 volume perfusion computed tomography examinations. Image quality (score, 1.0 vs 1.6; P < 0.01) was higher and the size of the signal loss was reduced significantly by iMAR (intracranial metal artifacts, 887 mm 2 vs 359 mm 2 [ P < 0.01]; cranial bolt, 3008 mm 2 vs 837 mm 2 [ P < 0.01]). Digital subtraction angiography confirmed vasospasms in 11 (92%) of 12 patients. Conclusion: The iMAR yields higher image quality by reducing artifacts compared with filtered back-projection.